The Genomic Landscape of Serrated Lesion of the Colorectum: Similarities and Differences With Tubular and Tubulovillous Adenomas - Tornillo, Luigi; Lehmann, Frank Serge; Garofoli, Andrea; Paradiso, Viola; Ng, Charlotte K. Y.; Piscuoglio, Salvatore (Frontiers in Oncology, 2021)
Serrated lesions of the colorectum are the precursors of 15-30% of colorectal cancers (CRCs). These lesions have a peculiar morphological appearance, and they are more difficult to detect than conventional adenomatous polyps. In this study we sought to define the genomic landscape of these lesions using high depth targeted sequencing. Eight sessile serrated lesions without dysplasia (SSL), three sessile serrated lesions with dysplasia (SSL/D), two traditional serrated adenomas (TSA) and three tubular adenomas (TA) were retrieved from the files of the Institute of Pathology of the University Hospital Basel and from the GILAB AG, Allschwil, Switzerland. Samples were microdissected together with the matched normal counterpart and DNA was extracted for library preparation. Library preparation was performed using the Oncomine Comprehensive Assay targeting 161 common cancer driver genes. Somatic genetic alterations were defined using state of the art bioinformatic analysis. Most SSLs, as well as all SSL/Ds and TSAs, showed the classical BRAF p.V600E mutation. The BRAF-mutant TSAs showed additional alterations in CTNNB1, NF1, TP53, NRAS, PIK3CA while TA showed a consistently different profile, with mutations in ARID1A (two cases), SMAD4, CDK12, ERBB3 and KRAS. In conclusion our results provide evidence that SSL/D and TSA are similar in somatic mutations with the BRAF hotspot somatic mutation as a major driver of the disease. On the other hand, TAs show a different constellation of somatic mutations such as ARID1A loss of function.